Aux origines d’une géopolitique de l’action spatiale : Michel Foucault dans les géographies françaises - Marc Dumont (L'Espace Politique)
The Intellectual work of Michel Foucault about the political space has been appropriated in different ways by the French geography. Debates around the discipline have to be characterized by a lack of understanding : in the seventies, geography was not yet ready to renew the dominant and specific analytical way of understanding space and politics : power is still identified with the State, space is understood as the national territory. The controversy in the first issue of the journal Herodote, is very instructive. From the 1980s, Claude Raffestin, geographer, develops a new geography of politics and power, in reference to Michel Foucault’s conceptions. Raffestin questions the relations between knowledge and power ; he write a story of geopolitics, which shows how this discipline is also an ideological discourse to justify the dominant power in his own nation. Raffestin will also theorize geography of political phenomena: a theory of space conceived as a field of power. Also geographer, Michel Lussault thinks in the 1990s a new use of Foucault. He supplements the classical notion of “actors system”, with the concept of "dispositif". He wants to keep on the role of images in political action and underlines the importance of norms in everyday individual action. With the work of this three generation of geographers, this article aim to clarify the meaning of French contemporary political geography, the emergence of several of its founding concepts: power, conflict...